Radio Astronomical Tools for the Study of Solar Energetic Particles I. Correlations and Diagnostics of Impulsive Acceleration and Particle Propagation - Klein, Karl-Ludwig (Frontiers in Astronomy and Space Sciences, 2021)
Solar energetic particles (SEPs) are sporadically ejected from the Sun during flares and coronal mass ejections. They are of major astrophysical interest, because the proximity of the Sun allows for detailed multi-messenger studies. They affect space weather due to interactions with electronics, with the Earth’s atmosphere, and with humans if they leave the protective shield of the magnetosphere of the Earth. Since early studies in the 1950s, starting with particle detectors on the ground, SEP events have been related to radio bursts. Two subjects are addressed in this chapter: attempts to establish quantitative correlations between SEPs and microwave bursts produced by gyro synchrotron radiation of mildly relativistic electrons, and the information derived from type III radio bursts on impulsive processes of particle acceleration and the coronal and interplanetary propagation. Type III radio bursts produced by electron beams on open magnetic field lines have a wide range of applications, including the identification of acceleration regions, the identification of confined particle acceleration with coronal signatures, but no SEPs, and the paths that the electrons, and energetic charged particles in general, take to travel from the low corona to the Heliosphere in case they escape. Simple scenarios of coronal particle acceleration are confirmed in relatively simple and short events. But the comparison with particle transport models shows that longer and delayed acceleration episodes exist especially in large SEP events. They will be discussed in a companion chapter.